Why Refashion? Fashion, Poetics and Hybridization of Creative Methods for a Sustainable Future. - Broega, Ana Cristina; Pardo Cuenca, Desamparados (Convergences - Journal of Research and Arts Education, 2025)
Although in the last 10 years, collaborative design and design for sustainability processes have been increasingly used, there is still a great lack of knowledge and precision in the development of precise collaborative methodologies and holistic applications of sustainable hybrid techniques that favor the development of co-creative and generative circular processes. The paradox of fast fashion and the pursuit of modernity, coupled with the need to care for the earth's resources in a sustainable manner that includes social, economic, and environmental impacts, is a dilemma to solve. Some studies have proposed exploring upcycling circular design processes; however, their methodological limitations and the absence of a clear and oriented design thinking process restrict them to seek the inspiration from textile waste in an artisanal perspective. These development processes are often imprecise in their methodology and accidental in their creation process, which generates little credibility, communicative security, and didactic replication in the classroom. In addition, the lack of precision and fine-tuning brings them closer to artisanal technical methods, lacking rigorous narrative logic and holistic design thinking. This research explored the design for sustainability processes, focusing on finding collaborative methodologies of rigorous design thinking that would help students explore and strengthen their individual and group identities by applying sustainable hybridization techniques throughout the design process. The focus was on how we educate designers for a sustainable and collaborative future. We built a collaborative methodological conceptual model of a sustainable approach that was tested in different projects over different academic years. The results demonstrate that the implementation of collaborative methodologies with sustainable approaches in the application of specific eco-design techniques and the construction of a group identity based on research, assignment analysis, and the use of creative techniques and tools that generate reflective learning contribute to the collaborative methodologies and the effective implementation of this methodology in the teachings of fashion design with a circular approach.